DAYA TERIMA, KADAR VITAMIN A DAN VITAMIN C ISTAN JAHE PLUS BUBUK WORTEL DAN SARI PEPAYA (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Consumption of nutritious food or drinks increases immunity so that it can prevent COVID 19. Ginger, carrot, and papaya are important in increasing immunity, so they must be developed into instant drinks. This study aims to determine the receptivity and levels of vitamin A and C Instant Ginger plus carrot powder and papaya extract (BWSP). The study used a post-test control group design, with three treatment groups of instant ginger with the addition of BWSP, each F1=0 percent, F2=50 percent, and F3=100 percent. The organoleptic test determines the receptivity aspects of colour, consistency, aroma, and taste. The spectrophotometer method determines vitamin A, iodometric method determines vitamin C. The results of the receptivity test showed the F2 treatment had the highest preference score in terms of colour (3.9 ± 0.74), aroma (3.4 ± 1.03), consistency (3.6 ± 0.66), and taste (3,7±0.90). The addition of BWSP affected the receptivity of instant ginger, both in terms of colour (p=0.002), aroma (p=0.030), consistency (p=0.006), and taste (p=0.003). The levels of vitamin A in instant ginger F2 reached 5810 mcg/100 ml and vitamin C 580 mg/100 ml. Adding BWSP at a concentration of 50 percent can increase the receptivity, vitamin A and vitamin C of ginger instant drink.